Reescribir la función : f(x) = 4(x-1)² -2 en la forma f(x) = ax²+bx+c
Respuestas a la pregunta
Contestado por
3
Respuesta:
La función en la forma f(x) = ax²+bx+c es f(x) = 4x²-8x +2
Explicación paso a paso:
Reescribir la función : f(x) = 4(x-1)² -2 en la forma f(x) = ax²+bx+c
Resolvamos:
f(x) = 4(x-1)² -2
f(x) = 4(x²-2x + 1) -2
f(x) = 4x²-8x +4 -2
f(x) = 4x²-8x +2
La función en la forma f(x) = ax²+bx+c es f(x) = 4x²-8x +2
Otras preguntas
Matemáticas,
hace 2 meses
Matemáticas,
hace 2 meses
Matemáticas,
hace 2 meses
Física,
hace 4 meses
Castellano,
hace 4 meses